Estudos dos efeitos das descargas atmosféricas nos índices de desempenho da subestação de Vila do Conde e subestação de Marabá - SANTOS, Luciano Silva dos (Universidade Federal do Pará, 2017)
This paper aims to present the effects of lightning in the performance indices in Vila do Conde substation (SE VDC) and Maraba (SE MB), which are situated in the north, in the state of Pará, integrating the North System - Eletronorte Transmission northeast, being connected to the Tucuruí Hydroelectric Power Plants (HPP Tucuruí). They were studied, establishing relations between the weather information provided by the SIPAM and data provided by central Eletronorte's operations in the period 2005-2013 in order to determine the harmful effects of lightning, which are responsible for the intensification of supply interruptions electricity. The analysis restricted to the area of operation of Eletronorte SE and SE VDC MB. The study developed evidence disconnections by lightning on transmission line VDC / CASTANHAL 230 KV and 500 KV breaker VCDJ7-08 and transmission line MB / Empress of 500 KV. The results demonstrate that a lightning strike may cause direct and indirect surges in transmission lines and high power substations. In this context it justifies the study of efficient forms of prevention, one of the purposes of this work.